Teknologi Pendidikan dalam Perspektif Islam: Integrasi Nilai, Etika, dan Inovasi Pembelajaran PAI - Yusriya Ni’matul ‘Izzah; Zia Achmalia Adela; Ahmad Mashuda; Ahmad Nurfalah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study discusses educational technology from an Islamic perspective through the integration of values, ethics, and innovation in Islamic Religious Education (PAI) learning. The study aims to analyze the role of educational technology in supporting the learning process of PAI in the digital era, which is characterized by the rapid development of information and communication technology. The method employed is qualitative research using a library research approach, drawing on various sources such as scientific journals, books, and relevant academic articles. The collected data were analyzed using content analysis techniques. The findings indicate that educational technology from an Islamic perspective functions not only as a learning medium but also as a means of instilling moral and spiritual values. The integration of Islamic values and ethics into technology-based learning can support character development, strengthen digital ethics, and enhance students' learning motivation and digital literacy. Therefore, the utilization of technology in PAI learning should be carried out wisely and remain grounded in Islamic principles in order to create learning that is innovative, relevant, and meaningful, while also addressing the challenges of education in the digital era.